Egyptian Journal of Biological Pest Control - El Husseini, Monir M.; El-Heneidy, Ahmed H.
This is a periodical scientific journal, published by the Egyptian Society for Biological Control of Pests (ESBCP) in collaboration with Springer publisher. The journal aims to publish an international peer-reviewed and high quality research articles in the field of biological and integrated pest control (Non-chemical control). The journal publishes review articles, original papers, conference reports, book review, editorials, laboratory reports, technical notes and short communication.